ACORN (A Clinically-Oriented Antimicrobial Resistance Surveillance Network) II: protocol for case based antimicrobial resistance surveillance - Mo, Y; Ding, Y; Cao, Y; Hopkins, J; Ashley, EA; Waithira, N; Wannapinij, P; Lee, SJ; Ling, CL; Hamers, RL; Roberts, T; Lubell, Y; et al. (F1000Research, 2023)
Background: Antimicrobial resistance surveillance is essential for empiric antibiotic prescribing, infection prevention and control policies and to drive novel antibiotic discovery. However, most existing surveillance systems are isolate-based without supporting patient-based clinical data, and not widely implemented especially in low- and middle-income countries (LMICs).